Narcissistic personalities: their virulence and characteristics (Research, Society and Development, 2022)
Objective as databases: to describe the narcissistic personality, exemplify what they are capable of doing, and explain their modus operandi, as well as their proximity to conductopathy. methodology: online searches were carried out for the construction of this article, which included the bvs/bireme, pubmed central, the cochrane library, web of science, google academic, as well as books on the subject, classified as gray literature, through the descriptors collected on the bvs/bireme platform corresponding to antisocial personality disorder; psychiatry; narcissism; criminology and depression to give scientific support to the statements obtained here and diluted in the text. results: narcissists are people who lack empathy, remorse, or any superior feeling toward other people. they need to control people or groups associated with them so that they are served and nourished with compliments, gifts, and amenities. the emotional and financial damage is often enough to devastate the person for the rest of his life, leading and in some cases to death. conclusions: narcissistic behaviorists are part of society and there is no cure for this personality disorder. supportive treatment must be offered to victims so that they are aware that these people exist to prevent or detect them as soon as possible.